HLA and killer cell immunoglobulin-like receptor (KIRs) genotyping in patients with acute ischemic stroke - Tuttolomondo, Antonino; Di Raimondo, Domenico; Pecoraro, Rosaria; Casuccio, Alessandra; Di Bona, Danilo; Aiello, Anna; Accardi, Giulia; Arnao, Valentina; Clemente, Giuseppe; Corte, Vittoriano Della; Maida, Carlo; Simonetta, Irene; et al. (Journal of neuroinflammation, 2019)
In humans, a major component of natural killer (NK) and T cell target recognition depends on the surveillance of human leukocyte antigen (HLA) class I molecules by killer immunoglobulin-like receptors (KIRs). To implement the knowledge about the immunological genetic background of acute ischemic stroke susceptibility in relation to the frequency of the KIR genes and HLA alleles. Subjects with acute ischemic stroke and subjects without stroke were genotyped for the presence of KIR genes and of the three major KIR ligand groups, HLA-C1, HLA-C2, and HLA-Bw4, both HLA-B and HLA-A loci. Between November 2013 and February 2016, consecutive patients with acute ischemic stroke were recruited. As healthy controls, we enrolled subjects without acute ischemic stroke. Subjects with acute ischemic stroke in comparison with controls showed a higher frequency of 2DL3, 2DL5B, 2DS2, and 2DS4 KIR genes and a lower frequency of HLA-B-Bw4 alleles. Subjects without acute ischemic stroke showed a higher frequency of interaction between KIR 2DS2 and HLAC2. We also observed a higher frequency of 2DL3 and 2 DL4 KIR genes in subjects with atherosclerotic (LAAS) subtype. Multiple logistic regression analysis showed a protective effect towards stroke of HLA-B-Bw4 and interaction between KIR 2DL2 and HLAC1 and 2DS2-HLAC2 and a detrimental effect of 2DL2-HLA-C1_A interactions. Our findings of a higher frequency of activating KIR genes seem to be consistent with findings previously reported patients with coronary syndrome. This higher frequency of "proinflammatory" genes in subjects with ischemic stroke could also explain the immunoinflammatory activation of the acute phase of stroke.